Cadmio complexes with biological activity: Scientific and technological prospection (Research, Society and Development, 2021)
Cadmium is a toxic metal from 12th group and 5th period of the periodic table. It’s common its use in batteries manufacturing and metal alloys production. It is absorbed by the organism of animals and plants causing risks to human health by bioaccumulation. Even with proven levels of toxicity, complexes involving this atom have biological activity according to several studies. As a study methodology, data were prospected in different databases for patents and the scientific papers published in the period up 1962 to 2021. Only 3 patents were found regarding the biological activity of complexes containing cadmium, although 3.257 results have been found for Cd (II) articles. The database with the highest number of published articles was Scifinder with 63% (2.037) of the articles. Few articles approached anthelmintic activity, showing that future research related to chemical substances containing this metal is a possibility in the new anthelmintic drugs investigation.